Dynamic Client Portfolios as Sources of Ambidexterity: Exploration and Exploitation Within and Across Client Relationships. Issue 3 (June 2016) - Bednarek, Rebecca; Burke, Gary; Jarzabkowski, Paula; Smets, Michael
Abstract : This paper explains how dynamic client portfolios can be a source of ambidexterity (i.e., exploration and exploitation) for knowledge-intensive firms (KIFs). Drawing from a unique qualitative dataset of firms in the global reinsurance market, we show how different types of client relationships underpin a dynamic client portfolio and become a source of ambidexterity for a KIF. We develop a process model to show how KIFs attain knowledge by segmenting their client portfolios, use that knowledge to explore and exploit within and across their client relationships, and dynamically adjust their client portfolios over time. Our study contributes to the literature on external sources of ambidexterity and dynamic management of client knowledge within KIFs.